Study on visual matching cognition of automobile interior and exterior. - Yingjie Huang; Bofan Zhang; Jiayu Liu (PLoS ONE)
This work aims to study the visual matching cognition of people with different professional backgrounds for automobile interiors and exteriors, using gasoline-powered automobiles and electric automobiles as the research objects. First, three classes of automobiles, B-class, C-class, and sport-type class automobiles, of different brands, with large differences in styling and styles, were taken as the experimental sample sources, and high-definition interior and exterior pictures of the two power types of automobiles were randomly selected as the experimental samples. The participants were then divided into expert and general user groups according to their professional background. The two groups of participants were asked to conduct a total of 3 groups of visual matching cognition experiments on the interior and exterior of gasoline-powered automobiles, electric automobiles, and automobiles mixed with the same number of gasoline-powered automobiles and electric automobiles. The statistical analysis of the data of the above three groups of experiments revealed that there was no significant difference between the two groups of participants in terms of the visual matching cognition of the interior and exterior of the gasoline-powered automobiles and electric automobiles. When the two types of automobiles were mixed for the experiment, the participants still showed visual matching cognition for the interior and exterior, but there were obvious differences in cognitive abilities between the two groups. Research has shown that both general users and experts have the ability to perform visual matching of automobile interiors and exteriors, however, the cognitive ability of general users is weaker than that of experts. The visual matching cognition of the automobile interior and exterior is not affected by the power type or the automobile type.